Building a Law of Human Rights: Roncarelli v. Duplessis in Canadian Constitutional Culture - Adams, Eric (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2010)
This article reveals how audiences, especially in anglophone Canada, initially received and interpreted Roncarelli v. Duplessis as a case, above all, about human rights. Ignoring the judgment’s myriad complexities, commentators eagerly situated the case within the Supreme Court of Canada’s “implied bill of rights” jurisprudence then taking shape. Part of the reason for the emphasis on Roncarelli’s rights can be traced to the manner in which Frank Scott and Louis Stein argued the case, and the language of rights employed by Justice Ivan Rand’s iconic judgment.But Roncarelli’s meaning also took shape in press accounts and editorials, radio broadcasts, case comments, and law school lectures. Exploring these often-neglected sources, this article exposes the role of constitutional culture in creating jurisprudential meaning. In turn, it also calls for greater recognition of the pre-Charter Supreme Court of Canada in contributing to Canada’s intellectual history of rights.